2015
DOI: 10.1682/jrrd.2014.04.0113
|View full text |Cite
|
Sign up to set email alerts
|

E-mental health preferences of Veterans with and without probable posttraumatic stress disorder

Abstract: Abstract-Mental health care practices supported by electronic communication, referred to as e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 69 publications
0
28
0
3
Order By: Relevance
“…was found in 9 out of 68 occurrences (13%) (12,14,16,17,25,26,33,34,37). Studies demonstrated that telehealth served as a means to reduce costs for both patients and providers.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…was found in 9 out of 68 occurrences (13%) (12,14,16,17,25,26,33,34,37). Studies demonstrated that telehealth served as a means to reduce costs for both patients and providers.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Eight out of 68 (12%) occurrences discussed "increased feelings of comfort, safety, and privacy" as a facilitator, meaning that veterans were particularly at ease with the use of telemedicine as a form of treatment (12,16,17,28,31,(35)(36)(37).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…telephone calls, CVT into the home or clinic, online computer-based interventions, personalized messages to computer, text messages to cell phone or social networking with a peer group). Veterans' willingness varied and depended on the technology and their PTSD screen status [13]. Veterans with probable PTSD were significantly less likely than those with no PTSD to report willingness for CVT in clinic (20.4% vs. 45.6%) or CVT in the home (25.5% vs 52.7%).…”
Section: Veteran Access To Mental Health Care Within the Us Departmenmentioning
confidence: 99%